Increased sliding of transverse abdominis during contraction after myofascial release in patients with chronic low back pain. (June 2016) - Chen, Yen-Hua; Chai, Huei-Ming; Shau, Yio-Wha; Wang, Chung-Li; Wang, Shwu-Fen
Abstract: Purpose: Recent evidence suggested the significance of integrity of the tension balance of the muscle-fascia corset system in spinal stability, particularly the posterior musculofascial junction which is adjacent to dorsal located paraspinal muscles joining each other at lateral raphe (LR). The purpose of this study was to compare the contraction of the transversus abdominis (TrA) at both anterior and posterior musculofascial muscle-fascia junctions in patients with low back pain (LBP) and asymptomatic participants before and immediately after a sustained manual pressure to LR. Methods: The present observational cohort study used a single-instance, test-retest design. The outcome variables included the resting thickness (Tr), the thickness during contraction (Tc), change in thickness (ΔT), sliding of musculofascial junction (ΔX), muscle length at rest (L) and displacement pattern (ΔD) of the TrA using ultrasonography. Vertical tolerable pressure at the LR was applied manual for 1 min. Tr, Tc, ΔT, and ΔX were analyzed by three-way ANOVA (musculofascial junction sites*group* pre-post manual release). ΔL and ΔD were analyzed by two-way ANOVA (group* pre-post manual release). Results: Participants with LBP revealed less Tc, ΔT and ΔX at both sites ( p < 0.005). After myofascial release, LBP group demonstrated a positive ΔD of the musculofascial junctions at both end ( p < 0.001). Nevertheless, both groups increased the ΔT and ΔX at both sites ( p < 0.001 and 0.001, respectively). Conclusion: The result indicated immediately effect of sustained manual pressure on musculofascial junction of TrA and supported the concept that the possible imbalanced tension of the myofascia corset of TrA in patients with LBP. Highlights: Increased change of thickness of TrA is noted after release in patients and control. Increased sliding is noted in the both ends of musculofascial junctions of the TrA. The musculofascial corset was shifted anteriorly in patients after release.